Anatomical distribution of sentinel lymph nodes in patients with endometrial cancer: a multicenter study. Issue 4 (2nd February 2022) - Restaino, Stefano; Buda, Alessandro; Puppo, Andrea; Capozzi, Vito Andrea; Sozzi, Giulio; Casarin, Jvan; Gallitelli, Vitalba; Murgia, Ferdinando; Vizzielli, Giuseppe; Baroni, Alessandro; Corrado, Giacomo; Pasciuto, Tina; et al.
Abstract : Objective: Sentinel lymph node (SLN) mapping represents the standard approach in uterine confined endometrial cancer patients. The aim of this study was to evaluate the anatomical distribution of SLNs and the most frequent locations of nodal metastasis. Methods: This was an observational retrospective multicenter study involving eight high volume gynecologic cancer centers in Italy. We reviewed 1576 patients with a histologically confirmed diagnosis of endometrial cancer from September 2015 to June 2020. All patients underwent total hysterectomy with salpingo-ophorectomy and SLN mapping. Results: A total of 3105 SLNs were mapped and removed, 2809 (90.5%) of these were bilateral and 296 (9.5%) unilateral. The overall detection rate was 93.4% (77.9% bilateral and 15.5% unilateral). The majority of SLNs (80%) and positive SLNs (77.8%) were found at the external iliac and obturator level in both endometrioid and non-endometrioid endometrial cancer. Negative SLNs were more frequent in patients with endometrioid compared with non-endometrioid cancer (91.9% vs 86.1%, p<0.0001). Older patients, a higher body mass index, and non-endometrioid histology were more likely to have 'no mapping' (p<0.0001). Univariate and multivariate analysis showed that higher body mass index and age at surgery were independent predictive factors of empty node packet and fat tissue (p=0.029 and p<0.01, respectively). Conclusion: The most frequent sites of SLNs and metastases were located in the pelvic area below the iliac vessel bifurcation. Our findings showed that older age, a higher body mass index, and non-endometrioid histology had a negative impact on mapping.